PERCOBAAN PENYULINGAN KAYU CENDANA (Santalum album L.) DARI KUPANG - Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Cendana oil, an essential oil extracted from Santalum album L. is an important non wood forest products from Indonesia. Recently, there has been a lot of inquiries on the quality of the oil obtained from different part of a tree and on the effect of processing condition on oil properties.In this study, the Santalum album L. wood was obtained from Kupang, Nusa Tenggara Timur province of Indonesia, where this wood is native to. The wood samples were prepared for further processing in two different sizes being those retained on and screened out wood particles of 40 mesh screen. The sample specimens were taken from trunk and root parts, then treated in three processing times. The yield and the chemical properties of the oil were measurea and recorded. A gas chromatography was employed in determining the santalol content of the oil and the result was analysed and evaluated.